Positive Psychology Interventions Addressing Pleasure, Engagement, Meaning, Positive Relationships, and Accomplishment Increase Well-Being and Ameliorate Depressive Symptoms: A Randomized, Placebo-Controlled Online Study - Gander, Fabian; Proyer, René T.; Ruch, Willibald (Frontiers in Psychology, 2016)
Objective: Seligman (2002) suggested three paths to well-being, the pursuit of pleasure, the pursuit of meaning, and the pursuit of engagement, later adding two more, positive relationships and accomplishment, in his 2011 version. The contribution of these new components to well-being has yet to be addressed. Method: In an online positive psychology intervention study, we randomly assigned 1,624 adults aged 18 to 78 (M = 46.13; 79.2% women) to seven conditions. Participants wrote down three things they related to either one of the five components of Seligman’s Well-Being theory (Conditions 1-5), all of the five components (Condition 6) or early childhood memories (placebo control condition). We assessed happiness (AHI) and depression (CES-D) before and after the intervention, and 1-, 3-, and 6 months afterwards. Additionally, we considered moderation effects of well-being levels at baseline. Results: Results confirmed that all interventions were effective in increasing happiness and most ameliorated depressive symptoms. The interventions worked best for those in the middle-range of the well-being continuum. Conclusion: We conclude that interventions based on pleasure, engagement, meaning, positive relationships, and accomplishment are effective strategies for increasing well-being and ameliorating depressive symptoms and that positive psychology interventions are most effective for those people in the middle range of the well-being continuum.